Scleroderma fibroblasts suppress angiogenesis via TGF-β/caveolin-1 dependent secretion of pigment epithelium-derived factor. Issue 3 (19th December 2017) - Liakouli, Vasiliki; Elies, Jacobo; El-Sherbiny, Yasser Mohamed; Scarcia, Margherita; Grant, Gary; Abignano, Giuseppina; Derrett-Smith, Emma C; Esteves, Filomena; Cipriani, Paola; Emery, Paul; Denton, Christopher P; Giacomelli, Roberto; et al.
Abstract : Objectives: Systemic sclerosis (SSc) is characterised by tissue fibrosis and vasculopathy with defective angiogenesis. Transforming growth factor beta (TGF-β) plays a major role in tissue fibrosis, including downregulation of caveolin-1 (Cav-1); however, its role in defective angiogenesis is less clear. Pigment epithelium-derived factor (PEDF), a major antiangiogenic factor, is abundantly secreted by SSc fibroblasts. Here, we investigated the effect of TGF-β and Cav-1 on PEDF expression and the role of PEDF in the ability of SSc fibroblasts to modulate angiogenesis. Methods: PEDF and Cav-1 expression in fibroblasts and endothelial cells were evaluated by means of immunohistochemistry on human and mouse skin biopsies. PEDF and Cav-1 were silenced in cultured SSc and control fibroblasts using lentiviral short-hairpin RNAs. Organotypic fibroblast–endothelial cell co-cultures and matrigel assays were employed to assess angiogenesis. Results: PEDF is highly expressed in myofibroblasts and reticular fibroblasts with low Cav-1 expression in SSc skin biopsies, and it is induced by TGF-β in vitro. SSc fibroblasts suppress angiogenesis in an organotypic model. This model is reproduced by silencing Cav-1 in normal dermal fibroblasts. Conversely, silencing PEDF in SSc fibroblasts rescues their antiangiogenic phenotype. Consistently, transgenic mice with TGF-β receptor hyperactivation show lower Cav-1 and higher PEDF expression levels in skin biopsies accompanied by reduced blood vessel density. Conclusions: Our data reveal a new pathway by which TGF-β suppresses angiogenesis in SSc, through decreased fibroblast Cav-1 expression and subsequent PEDF secretion. This pathway may present a promising target for new therapeutic interventions in SSc.